Green Construction Material: Polyethylene Waste Reinforce Concrete for Panel Application - Andrie Harmaji; Siswanti Zuraida (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
Plastic Composite Panel (PCP) is an innovation in the field of materials that uses recycling plastic waste to construct composite cement panels. This material innovation is one of the solutionto answer environmental problems caused by plastic waste. Some previous studies mostly used plastic waste for concrete aggregates. Thus, making this study different from previous studies. The purpose of this study is to make a prototype of a PCP that is environmentally friendly with panel dimensions sample of 100 x 30 x 10 mm thick. The method used is an experimental test using materials in the form of polyethylene terephtalate (PET) from used water bottle and cement waste as well as testing its physical and mechanical properties carried out in the laboratory. Variations in PET used for testing materials are 0- 20%. In addition to mechanical properties, specific gravity and porosity test is carried out. The best results shows that 5% PET addition to cement paste increase the flexutral strength to 4.47 MPa compared to control sample which has 3.26 MPa. Porosity test shows that addition of 10% PET reduce the density of PCP to 63.64% compared to control sample that has 44.44%.